Aortic root and hemiarch replacement in a patient with Loeys–Dietz and hypoplastic left heart syndromes. (11th October 2017) - Mohamed Ahmed, Eltayeb; Visan, Alexandru Ciprian; Stuart, Graham; Stoica, Serban
Abstract: A 15-year-old patient with hypoplastic left heart syndrome underwent 3-stage palliation by the age of 3 years. He was later diagnosed with Loeys–Dietz syndrome. On follow-up imaging, the neoaorta was dilated at 50 mm in diameter. He underwent aortic root replacement with a composite valve conduit and hemiarch replacement, using a boat-shaped Dacron graft. The uncertainty of how univentricular circulation would tolerate long bypass time steered us away from a total arch replacement. His postoperative recovery was uneventful. Imaging postoperatively demonstrated stable dilatation of the aorta distal to the hemiarch replacement. Considering the risk of reintervention, we elected to monitor the distal aorta. The combination of Loeys–Dietz syndrome and hypoplastic left heart syndrome presents unique challenges, rarely reported in the literature.